Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.3168/jds.s0022-0302(05)73001-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Freezing Point of Blood and Milk During Dehydration and Rehydration in Lactating Cows

Abstract: We studied the influence of short-term changes in water intake in 4 lactating Holstein cows on diurnal fluctuation of packed cell volume (PCV), freezing point of blood (FPblood), freezing point of milk (FPmilk), and the relationship between changes in FPblood and FPmilk. The experiment lasted 108 h and was divided into 3 periods: 1) control (38 h); 2) dehydration/rehydration with 4 consecutive 12-h sequences: 8 h without water, 0.5-h access to water, 1.5 h without water, and 2-h access to water; and (3) 22 h f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
6
12
1
Order By: Relevance
“…-0.565, p<0.01). Bjerg et al (2005) reported that the highest and lowest freezing point in storage tanks occurred in summer and winter respectively that matches with this study. According to the findings of present study, higher limits of temperature, sunshine hours and increase of consumed water through the longer days would be among the reasons that increased the freezing point of milk in the summer time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…-0.565, p<0.01). Bjerg et al (2005) reported that the highest and lowest freezing point in storage tanks occurred in summer and winter respectively that matches with this study. According to the findings of present study, higher limits of temperature, sunshine hours and increase of consumed water through the longer days would be among the reasons that increased the freezing point of milk in the summer time.…”
Section: Discussionsupporting
confidence: 91%
“…Azad et al (2007) reported no significant differences for milk specific gravity in different months of the year in Bangladeshi cows (p>0.05) that is inconsistent with the findings of present study. Ozrenk and Selcuk Inci (2008) reported no significant seasonal effects on specific gravity of milk whereas at present study the highest and the lowest gravities were observed in February (1.0288g/cm 3 ) and October (1.0262g/cm 3 ) respectively (average 1.026g/cm 3 ). There was also a significant difference for microbial loads of the milk immediately stripped from udder in all seasons except autumn in both systems of traditional and industrial dairy farms at present study (table 2, p<0.01).…”
Section: Discussioncontrasting
confidence: 58%
“…The average value of FP in our study decreased in the summer, most probably as a result of high temperatures in the surrounding environment and short-term dehydration of the animals, as also reported by Bjerg et al (2005). Early in month 11 when the grazing season ended with reduced milk production, FP value was the lowest, corresponding to a higher content of solids also reported by Kuchtík et al (2008).…”
Section: Discussionsupporting
confidence: 63%
“…The effect of high environmental temperatures and organism dehydration can also be the causes of this FP reduction. Bjerg et al (2005) reported a reduction in FP of milk due to short-term dehydration. In autumn, in months 9 and 10, the detected values were -0.5513 ± 0.0022°C and -0.5514 ± 0.0042°C.…”
Section: Resultsmentioning
confidence: 99%